Development of Contextual-Based Learner Worksheets to Improve Critical Thinking Skills in Geometry - Nurhikmah; Fitriani Nur; Ilyas, Ilyas (Alauddin Journal of Mathematics Education, 2024)
The purpose of the study was to determine the process of developing context-based LKPD to improve critical thinking skills on geometry material and to determine the quality of LKPD that meets the criteria of valid, practical and effective. The research subjects were students of class IX SMP 40 Makassar consisting of one class, the instruments used in this study were validation sheets, student response questionnaires, teacher response questionnaires, student activity observation sheets, LKPD implementation observation sheets and critical thinking skills tests. The results of this study are (1) Development of contextualised LKPD using the ADDIE model which consists of five stages, namely (Analysis) Identifying existing problems to understand the needs of LKPD, (Design) Designing LKPD suitable for use in the schools tested, (Development) Developing LKPD based on input from validators and preparing research instruments, (Implementation) Applying LKPD directly in learning activities, and (Evaluation) Evaluating the feasibility of LKPD. (2) The results of the validation of the LKPD show a score of (3.69) with a very valid category. The practicality obtained from the teacher response questionnaire of (4.46) with a very good category and the results of the analysis of the LKPD implementation observation sheet of (1.82) with the category fully implemented which shows that this LKPD is practical. The effectiveness of the LKPD is indicated by the student activity observation sheet (71.40%), the student response questionnaire (3.95) and the critical thinking test (72.36%), so this LKPD is declared effective for learning.